CMET-40. LONG-LASTING RESPONSE IN SPINAL METASTASES FROM ALK REARRANGED NON-SMALL-CELL LUNG CANCER TREATED WITH DIFFERENT ALK INHIBITORS. (5th November 2018) - Pellerino, Alessia; Rudà, Roberta; Franchino, Federica; Marchese, Giulia; Bruno, Francesco; Mo, Francesca; Soffietti, Riccardo
Abstract: INTRODUCTION: About 40% of ALK-rearranged NSCLC patients develop brain metastases (BM), while leptomeningeal metastases (LM) occur in 5% of patients, and spinal intramedullary metastases in < 1%. Few data are available regarding the efficacy of ALK inhibitors in neoplastic spinal disease from NSCLC. CASE-REPORT: In March 2014 a 55 year-old woman developed multiple BM after 2 years from the diagnosis of an ALK-rearranged NSCLC who was receiving crizotinib. Crizotinib was continued associated with WBRT with a near-CR (RANO criteria) lasting 12 months. One year later a spinal MRI displayed multiple intramedullary enhancing lesions and diffuse leptomeningeal spread along the cauda equina, with CSF positivity for neoplastic cells. Ceritinib was started and a CR both on MRI and CSF was obtained lasting 18 months. In December 2017 the patient developed bladder dysfunction and paralytic ileus due to multiple intramedullary spinal and leptomeningeal recurrences. Considering the higher BBB penetration of lorlatinib, the patient started the drug and achieved a significant improvement of the urinary incontinence and intestinal transit after 3 months. Conversely, no change of the extent of spinal disease was observed on MRI. At this time, the patient is continuing treatment with lorlatinib and she is free of recurrence since 5 months. DISCUSSION: The development of CNS disease in ALK-rearranged NSCLC has been suggested to be a natural evolution of the disease and/or is correlated to low CNS penetration of the molecular drugs that control the systemic disease. The PROFILE trials have shown longer OS in patients with BM who received crizotinib beyond progression, but data are lacking on the activity of second- and third-generation ALK inhibitors. CONCLUSION: This is the first report of a prolonged clinical and radiological response using sequentially different ALK inhibitors in a patient with concurrent LM and spinal intramedullary metastases from an ALK-rearranged NSCLC.